Effect of Tourism Supply Chain Practice on Marketing Performance: SMEs Cases - SUTEJA, Usep; SUGANDINI, Dyah; ISTANTO, Yuni (Journal of Environmental Management and Tourism, 2020)
Research on tourism supply chain management is still rare. However, this research is needed by tourism agents and the government. This study aimed to analyze the influence of supply chain integration, marketing orientation of supply chain practices on marketing performance. The data used in this study amounted to 206. Respondents in this study were tourism managers in Yogyakarta, Indonesia. Data analysis techniques using SEM-AMOS. The results of this study indicate that the model is acceptable. Good supply chain practices that are significantly applied help tourism businesses to improve their marketing performance. Marketing orientation and supply chain integration are also crucial in influencing marketing performance. This research contributes to previous theories about applying supply chains in tourism, especially in Indonesia and developing countries, because the uniqueness of tourism in each region requires a different study.